New technologies and reference services - Katz, Linda Sternberg (Routledge, 2019)
Offer your patrons the cutting-edge reference services they demand! In the past, a reference librarian needed to develop a command of a few reference works, master the skills of the reference interview, and interface with library users in person or via telephone. Today's reference librarian is faced with much, much more. New Technologies and Reference Services suggests ways you can tame the information explosion and take advantage of new technologies. This comprehensive volume recounts the ways reference librarians have adapted traditional services to deal with the changes in both information technologies and library patrons. New Technologies and Reference Services offers tested techniques for fostering information literacy in patrons daunted by the high-tech edge of the new library. Even computer-savvy younger students may need help learning specialized searching skills. This practical volume suggests several innovative ways to teach those skills using interactive classrooms, drop-in seminars, and required courses. New Technologies and Reference Services discusses the other implications of new technologies, including: developing trends in publishing, including value-added services and the death of the printed encyclopedia the effects of CD-ROM, electronic publishing, and the Internet on copyright issues videoconferencing at the reference desk collection strategies and budgets in an era of multiple formats decentralizing library reference services information apartheid, the growing gap between the information haves and have-notsThis helpful volume gives practical, tested advice and ideas on the broader issues of information technology. With plentiful Web addresses, New Technologies and Reference Services presents new ideas sure to make your job easier.